A representação de personagens gays na coletânea de contos Stud e em sua tradução "As aventuras de um garoto de programa" - Adail Sebastiao Rodriues Junior (2006)
Based upon a discursive tradition of Translation Studies, more specifically a hallidayan model for textual analysis, this dissertation aims at unveiling how gay characters are represented in a collection of short stories entitled Stud and firstly published in the 1960s in The United States of America, as well as in its translation entitled As Aventuras de um Garoto de Programa, which was done around thirty years later in Brazil. The transitivity system was chosen as a linguistic resource tomake visible the way gay characters represented their world experiences through their actions, behaviours, feelings, relations and speeches. Systemic functional grammar has been used by a broad range of scholars in the field of Translation Studies, who are interested in understanding principally literary translation from a discursive perspective. Regarding gay literature, however, the transitivity systemhas not yet been applied to investigating the way gay characters are represented through first person narrative. So, this work, besides focussing on the system of transitivity of an English/Portuguese corpus of a collection of gay stories, also uses WordSmith Tools software to quantify the data as well as analyse it discursively. The methodology adopted followed the following steps: (i) the whole corpus was scanned and corrected; (ii) after that, the corpus was manually tagged in order toshow what role the narrator or any other gay character played in the stories that is, if the gay characters were acting, behaving, feeling, thinking, speaking, and so forth, according to the process (verb) linked to each one of them; (iii) finally, the gay personages were investigated through the narrator's point of view, since the short stories are narrated through a first person standpoint, with a participating narrator. The analyses carried out strikingly show there is a higher frequency ofprocesses that represent human participants acting upon the world, and parts of the characters bodies, interpreted as abstract agents or participants, which act upon the world as well. The results also point to the application of some other theoretical possibilities to the investigation pursued in this dissertation, mainly the ideological values and interests that lie behind the original publication of Stud in the U.S. and its translation about thirty years later in Brazil.